APPLICATION OF MODERN METHODS TO INTENSIFY HYDROCARBON PRODUCTION - Sultonov Nodir Normurodovich; Asadova Hulkar Boymanovna (Galaxy International Interdisciplinary Research Journal, 2021)
The article briefly describes the results of the oil and gas industry in recent years and some problems, negative trends associated with objective and subjective reasons, and their consequence, such as reducing the volume of oil and gas condensate production and natural gas. In addition, the technology to increase production efficiency through the use of rational field development systems, the widespread introduction of modern methods such as hydraulic fracturing.